Early growing season weather variation, expectation formation and agricultural land allocation decisions in Ethiopia. (18th August 2022) - Ahmed, Musa Hasen; Tesfaye, Wondimagegn Mesfin; Gassmann, Franziska
Abstract: Using unique crop‐specific data gathered over 7 years, we study if and how maize‐producing farmers in Ethiopia adjust their land allocation decisions in response to pre‐planting‐season weather variations. We show that farmers adjust their land allocation decisions in response to increased temperatures early in the growing season. In addition to quantifying a substantial adaptation margin that has not been documented before, our study also reveals the presence of a weather variation‐induced expansion of maize production into areas that are less suitable for maize cultivation.